FAMILY STRUCTURE, WOMEN'S EDUCATION AND WORK: RE-EXAMINING THE HIGH STATUS OF WOMEN IN KERALA - Mridul Eapen and Praveena Kodoth (Centre for Development Studies-WP341, 2002)
Literacy, together with non-domestic employment, which gave women access to independent sources of income, have been regarded as important indicators of women's `status', which affected fertility and mortality outcomes. Since women in Kerala have on average, been the most literate when compared with women in other states of India (though the same could not be said of female work-participation rates), much has been written about their `high status' and their central role, historically, in social development. However, there is a growing uneasiness with Kerala's social development outcomes linked to non conventional indicators as in the rising visibility of gender based violence, mental illhealth among women, and the rapid growth and spread of dowry and related crimes. We suggest that engagement with socio-cultural institutions such as families, which mediate micro level decisions regarding education, health or employment, could reveal the continuities rather than disjunctures between conventional social development outcomes and non conventional indicators of ill health and violence. Changes in the structure and practices of families in Kerala in the past century have had wide-ranging implications for gender relations. Alterations in marriage, inheritance and succession practices have changed dramatically the practices of erstwhile matrilineal groups as well as weakened women's access to and control over inherited resources. Alongside, women's education and employment have not played the transformative role so generally expected of them. Changing levels of female employment and the persistence of a gendered work structure have limited women's claims to "self-acquired" or independent sources of wealth. Underlying these changes are conceptions of masculinity and femininity, which privilege the male working subject and female domesticity.